Antioxidant activity and quantification of phenols, flavonoids and total tannins of Cinnamomum triplinerve (Lauraceae) - Silva, Ana Francisca Gomes; Pezenti, Letícia; Abel, Mayara Cristina Neves; Yunes, Rosinara Virgínia Ferreira (Ciência e Natura, 2019)
The present study evaluated the antioxidant activity and determined the total phenolic, flavonoid and tannin contents of the extracts from leaves, barks and fruits of Cinnamomum triplinerve. The antioxidant activity was evaluated by the 2,2-diphenyl-1-picrylhydrazyl radical (DPPH) free radical scavenging method and the quantification of total phenols, flavonoids and tannins by spectrophotometry in the visible region. The extract from the barks was the most active in relation to the antioxidant activity (IC50 11.42 ± 0.41 μg/mL) and also the one with the highest total phenol content (36.38 ± 1.11 mg EAG/g extract) and total tannins, 14.58 ± 1.48 mg EAT/g extract. The results suggest that the antioxidant activity of C. triplinerve is mainly related to the presence of phenolic compounds, such as flavonoids and tannins, which are included in the category of free radical scavengers and efficient in the prevention of oxidative processes.